Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Disponible en ligne à l'adresse: https://doi-org.proxy.bibliotheques.uqam.ca/10.1002/9781118896877.wbiehs364
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques